Mast cell diseases in practice and research: issues and perspectives raised by patients and their recommendations to the scientific community and beyond - Jennings, Susan V.; Finnerty, Celeste C.; Hobart, Jessica S.; Martín-Martínez, Mercedes; Sinclair, Kristin A.; Slee, Valerie M.; Agopian, Julie; Akin, Cem; Álvarez-Twose, Ivan; Bonadonna, Patrizia; Bowman, Angela S.; Brockow, Knut; et al. (The journal of allergy and clinical immunology. In practice, 2022)
Background - Since 2010, patients and physicians have collaborated to understand unmet needs of patients with mast cell diseases, incorporating mastocytosis and mast cell activation disorders, which include mast cell activation syndromes. - Objective - This Open Innovation in Science project aims to expand understanding of the needs of patients affected by mast cell diseases, and encourage global communication among patient advocacy groups, physicians, researchers, industry, and government. A major aim is to support the scientific community’s efforts to improve diagnosis, management, therapy, and patients’ quality of life by addressing unmet needs. - Methods - In collaboration with mast cell disease specialists, 13 patient advocacy groups from 12 countries and regions developed lists of top patient needs. A core team of leaders from patient advocacy groups collected and analyzed the data and proposed possible actions to address patient needs. - Results - Findings identified similarities and differences among participating countries in unmet needs between patients with mastocytosis and those with mast cell activation syndromes. Issues emphasized struggles relating to the nature and rarity of mast cell diseases, their impact on quality of life, the diagnostic process, access to appropriate care, more effective treatment, and the need for research. - Conclusions - Solutions vary across countries because situations differ, in particular regarding the existence of and access to centers of excellence and reference centers. Multifaceted mast cell activation syndrome barriers necessitate innovative approaches to improve access to appropriate care. The outcomes of this project should greatly support scientists and clinicians in their efforts to improve diagnosis, management, and treatment of patients with mastocytosis and mast cell activation disorders.
Online verfügbar: 28 June 2022, Artikelversion: 9 August 2022
Gesehen am 23.10.2023